Can body composition be used to optimize the dose of platinum chemotherapy in lung cancer? A feasibility study - Crosby, Vincent; D'Souza, Catherine; Bristow, Carina; Proffitt, Amy; Hussain, Asmah; Potter, Vanessa; Hennig, Ivo M.; O'Connor, Richard; Baracos, Vickie E.; Wilcock, Andrew (Springer, 2016)
Purpose Current methods of dosing platinum-based chemotherapy are suboptimal. Potentially, taking lean body mass into account may help. To inform the design of a future study, we first examined the feasibility and acceptability of such an approach using dual-energy X-ray absorptiometry (DEXA) and explored aspects suggestive of over- and under-dosing. Methods Patients with lung cancer offered platinum-based chemotherapy over 1 year were identified and, if eligible, invited to take part in a prospective feasibility study. Questionnaires examined acceptability of the DEXA scan and of a future study that randomized between traditional dosing and one adjusted according to body composition. Dose-limiting toxicity (DLT) and a lack of neutropenia explored potential over- and under-dosing, respectively. Results Of the 173 patients offered chemotherapy, 123 (71%) were ineligible, mostly because of failing entry criteria (84, 49%). Of the 50 approached, 18 (36%) participated, most receiving carboplatin, with 17 providing data. All found a DEXA scan acceptable; other assessments were fully completed, except nadir and pre-chemotherapy blood counts. Most (94%) were prepared to take part in a future study, although the additional hospital visits for a nadir blood count were unpopular with some. Five (29%) patients experienced six episodes of DLT which resulted in discontinuation (3), dose reduction (2) or change to a less toxic regimen (1). Nine (60%) patients experienced either no (2) or inconsistent (7) neutropenia. Conclusions A randomized trial appears acceptable and feasible in patients receiving carboplatin. Adjustment of our entry criteria and avoiding a hospital visit for a nadir blood count should aid recruitment.